Pengembangan Desain Pembelajaran Matematika Menggunakan Model Dick & Carey Pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV) - Zanuar Renaldie; Ade Syfhia Ahzrani; Avita Anggraini; Bayu Aji (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This article describes the development of Dick & Carey's learning design model on the Carey on the material of Linear Equation System Two Variables (SPLDV) Class X Senior High School.The purpose of this research is to explain the stages of the development of the Dick & Carey development stages of Dick & Carey learning design in designing effective and structured learning in the context of mathematics learning on and structured in the context of mathematics learning on the material of the System of Linear Equations Two Variables (SPLDV) Class X SMA. Two Variable Linear Equation (SPLDV) material. As for the results of the development of learning design Dick & Carey's learning design development results provide a success in learning objectives. This learning model provides a systematic and structured stage process for teachers in making plans for structured for teachers in making plans or designs in the implementation of learning. implementation of learning. This learning model also emphasizes on achievement of specific learning objectives and evaluation of learning outcomes. learning outcomes. This article provides an overview of the importance of developing learning design model to achieve success in student learning process.